2015
DOI: 10.1111/cbdd.12685
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New ‘Hybrid’ Compounds Based on Benzofuroxans and Aminoalkylnaphthalimides

Abstract: Pathogenic bacteria and fungi eventually develop resistance to existing drugs, and therefore, we need constant development of new drugs. The research is aimed at addressing fundamental scientific problems-the search for new biologically active compounds among several benzofuroxan-containing 'hybrid' products. N-substituted naphthalimides were chosen as a second pharmacophore. Benzofuroxanes biological effects were studied by means of bacterial lux-biosensors. Compounds IIIa, IVa, IIIc, and IVc displayed more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…As in the previously illustrated examples [12,13], the obtained results indicate that the reactivity of two chlorine atoms in benzofuroxan 1 towards nucleophilic substitution differs significantly. The substitution occurred in the position 4 of the benzofuroxan 1 solely regardless of the reactants ratio, reaction time and the temperature.…”
Section: Synthesissupporting
confidence: 81%
See 1 more Smart Citation
“…As in the previously illustrated examples [12,13], the obtained results indicate that the reactivity of two chlorine atoms in benzofuroxan 1 towards nucleophilic substitution differs significantly. The substitution occurred in the position 4 of the benzofuroxan 1 solely regardless of the reactants ratio, reaction time and the temperature.…”
Section: Synthesissupporting
confidence: 81%
“…Molecular modification is a rather promising strategy in the development of drug analogues with better bioavailability, higher biological activity, and less toxicity. Special attention is currently paid to the "hybrid" compound containing benzofuroxan and another biologically active subunit in one molecule [3,12,13]. Evaluation in vitro and in vivo of levels of prostaglandin E2 and thromboxane B2 decrease in the blood plasma samples of a compound obtained by binding of diclofenac and benzofuroxan fragments showed that after adding of benzofuroxan scaffold, this compound retains the pharmacological characteristics of Diclofenac, including anti-inflammatory activity, without the deleterious gastrointestinal effects which is normally present in the prototype [14].…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies were performed on these samples by means of bioluminescent bioreporter E. coli (Lux) strains in order to assess the ability of these solid catalysts to generate mutagenic species and/or cytotoxic ROS (Chugunova et al, 2015(Chugunova et al, , 2016.…”
Section: Decontamination From Blistering and Nerve Agent Simulantsmentioning
confidence: 99%
“…Finally, aiming at a real on-field use, where a total-loss dispersion of solid decontamination mixtures is likely, the potential impact of the catalysts on the environment was evaluated by three main kinds of biotests, as rapid, costeffective and sensitive screening tools: (i) the marine bioluminescent bacterium, P. leiognathi Sh1, isolated from Azov Sea, was utilised as a target organism to assess the direct toxic impact on living organisms (Katsev, 2014;Kuryanov, Chupakhina, Shapovalova, Katsev, & Chirva, 2011); (ii) the potential mutagenic properties of the solids and their ability to generate toxic oxygen radicals were evaluated by luminescent bioreporter strains of Escherichia coli MG1655, with the lux CDABE operon from Photorhabdus luminescens (Chugunova et al, 2016(Chugunova et al, , 2015Zavilgelsky, Kotova, Yu, & Manukhov, 2007); and (iii) the potential detrimental impact of the solids on vegetable plants was evaluated by studying the effects on the chlorophyll fluorescence and on germination parameters on P. vulgaris L., as a model plant (common bean plants) (Maxwell & Johnson, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, a huge number of benzofuroxan derivatives have been studied and described, which show a wide range of biological activity [ 5 , 6 , 7 , 8 ]. The synthetic potential of benzofuroxans is determined by the easiness of introducing into their structure, while maintaining the furoxan ring, various pharmacophore groups responsible for the appearance of biological activity, as well as obtaining on their basis a wide range of different classes of NO-containing heterocyclic compounds [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%